Control of Cerebral Blood Flow by Blood Gases - Duffin, James; Mikulis, David J.; Fisher, Joseph A. (Frontiers in Physiology, 2021)
Cerebrovascular reactivity can be measured as the cerebrovascular flow response to a hypercapnic challenge. The many faceted responses of cerebral blood flow to combinations of blood gas challenges are mediated by its vasculature’s smooth muscle and can be comprehensively described by a simple mathematical model. The model accounts for the blood flow during hypoxia, anaemia, hypocapnia and hypercapnia. The main hypothetical basis of the model is that these various challenges, singly or in combination, act via a common regulatory pathway: the regulation of intracellular hydrogen ion concentration. This regulation is achieved by membrane transport of strongly dissociated ions to control their intracellular concentrations. The model assumes that smooth muscle vasoconstriction and vasodilation and hence cerebral blood flow, are proportional to the intracellular hydrogen ion concentration. Model predictions of the cerebral blood flow responses to hypoxia, anaemia, hypocapnia and hypercapnia match the form of observed responses, providing some confidence that the theories on which the model is based have some merit.